Analysis on The Effect of Intellectual Capital on Growth and Financial Performance of Islamic Banking - Jetmiko Jetmiko (Indonesian Journal Of Business And Economics, 2018)
This research aims to analyze the influence of Intellectual Capital and Financial Performance using Partial Least Square Approach. The sample of this research is 19 Islamic Banks in Indonesia, Malaysia and GCC countries. Partial Least Square analysis model was employed to test the hypotheses. The result of this study shows that intellectual capital disclosure affects the Islamic banks’ financial performance in Indonesia and GCC countries but not those in Malaysia. As for the company’s growth, the disclosure of intellectual capital does not have effect on the company’s growth. The influence of the disclosure of intellectual capital on financial performance could mean that the company should give more attention to the quality of intellectual capital.